Quantitative Characterization of the Perforation Behaviour of Direct Recycled Aluminum Alloy 6061 Plates Subjected to High-Velocity Impact - Farhan Latif, Irfan Alias; Mohd Nor, Mohd Khir; Yusuf, Nur Kamilah; Subramaniyan, S Kanna; Abdul Samad, Mohd Syazwan; Ma’at, Norzarina (semarak ilmu, 2024)
This study aims to establish the perforation behaviour of direct recycled AA6061 to help establish the properties of the current most optimized direct recycled AA6061 through the hot press forging technique. This was achieved by subjecting direct recycled AA6061 plates of varying thickness to high-velocity impacts using a single-stage gas gun setup. The impactor is a hemispherical steel projectile of 13mm in length and 8.5mm in diameter. Plates of 3,4,5 and 10mm thickness were tested at velocities ranging from 120 m/s to 402 m/s. The deformation profiles of the impacted plates were captured and analyzed to quantitatively establish the perforation behaviour of recycled AA6061 plates. The plates showed irregular and non-axis symmetric patterns of deformation hinting the material exhibits anisotropic properties. The changes in the deformation profile were investigated in relation to changes in impact velocities and plate thickness were made to understand how they impact the profile. The deformation area was observed to be decreasing when the bullet impact velocity was increased. Higher velocity impact events lead to more material ejection from the plate in the form of fragmentation. Additionally, the deformation zone was observed to be getting smaller with an increase in the thickness of the plate. Thicker plates were found to have more fragmentation compared to thinner plates. Ductile failure characteristics such as petal formation and plugging were observed along with brittle characteristics such as fragmentation and conal fractures. Lower-velocity impacts lead to more energy absorbed by the target plates. Thicker plates observed more of the bullet’s energy. Through experimentation, the deformation behaviour of the directly recycled AA6061 material was established. This data can be used as a base for further research into the material’s behaviour characterisation.